2019
DOI: 10.21315/mjms2019.26.6.12
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of a Mental Health Literacy Programme for Refugee Teachers in Malaysia

Abstract: BackgroundChildren and young refugees often experience negative events that affect their mental health. Their caregivers may also be in the same predicament, implying that the teachers in schools are a potential source of help and support. However, most teachers have little understanding of mental health and are, thus, clueless in helping their students. To address this need, a newly developed one-day mental health literacy programme was conducted among 68 refugee teachers in Malaysia.MethodsParticipants learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The current study population scored an average mental health literacy level of 43.82. This is comparable to a separate study among Malaysian teachers by Tay et al, with a mean score of 42.32 [ 35 ]. The study sample scored relatively higher than the Lebanese community but lower than studies in Jordan and the United Kingdom [ 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…The current study population scored an average mental health literacy level of 43.82. This is comparable to a separate study among Malaysian teachers by Tay et al, with a mean score of 42.32 [ 35 ]. The study sample scored relatively higher than the Lebanese community but lower than studies in Jordan and the United Kingdom [ 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…Forced to be self-supporting, the teachers at community-run learning centers tend to be refugees themselves. This essentially puts the teachers' psychosocial wellbeing at risk as they too have gone through hardships and conflicts (Letchamanan, 2013;Tay et al, 2019). However, Kok et al (2013) discovered that teachers are happy to work and teach for the good of the children's future; that they are proud of their work and believe that it would contribute to the greater good of the community.…”
Section: Educationmentioning
confidence: 99%
“…Additionally, a six-session intervention with refugees from Myanmar identified that multiple modalities had beneficial effects on mental health (Tay et al, 2020). An 8-week mental health intervention implemented among women from Afghanistan also led to improved mental health (Shaw et al, 2019), and an intervention for refugee teachers led to increases in mental health literacy (Tay, Ong, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Program and policy efforts seek to improve health and mental health services among displaced populations in Malaysia. Multiple group and community interventions have positively influenced mental health outcomes (James et al, 2021; Tay et al, 2020; Tay, Ong, et al, 2019). For example, 3-day community workshops addressing partner violence and help-seeking led to increased intent to seek mental health resources (James et al, 2021).…”
Section: Introductionmentioning
confidence: 99%